Analisis Kritik Sosial dalam Kumpulan Cerpen Matinya Tukang Dongeng Karya Soni Farid Maulana - Adelia, Sita; Putrayasa, Ida Bagus; Artawan, Gde (Jurnal Penelitian Mahasiswa Indonesia, 2024)
This study aims to describe 1) the form of social criticism in the collection of short stories Matinya Tukang Dongeng, 2) the form of conveying social criticism in the short story collection Matiya Tukang Dongeng, and. Qualitative design is employed as the framework for this research. The method used in collecting data is literature study and interviews. This study uses data identification, data analysis techniques, namely data reduction, data presentation, concluding, and verification. The results of this study indicate that: (1) Forms of social criticism found as many as 61 data, namely: 4 data on poverty issues, 16 data on crime problems, 11 data on political issues, 19 data on religion,, 2 data on education problems, 6 data on family disorganization problems, and 3 data on war issues, 2) Forms of delivery of social criticism totaling 61 data, consisting of 30 data of direct delivery forms and 31 data of indirect delivery forms including 3 data of cynical delivery forms, 22 interpretive forms of delivery, and 6 symbolic forms of delivery.